PERENAPAN MODEL PEMBELAJARAN SOMANTIS AUDITORI VISUAL INTELEKTUAL (SAVI) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SDN CIPARAY - Mulyana, Rohmat; Pratama, Febri Fajar; Z, Rizki Hadiwijaya (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
This study was motivated by the low level of active student participation in the learning process. It is a Classroom Action Research (CAR) conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. Data collection techniques included observation, interviews, and documentation, while the data were analyzed using both quantitative and qualitative approaches. The purpose of this research was to improve students’ learning engagement through the implementation of the Somatic, Auditory, Visual, and Intellectual (SAVI) learning model in the Pancasila Education subject for fifth-grade students at SDN Ciparay. The findings indicate a significant increase in students’ active participation. In the pre-cycle condition, only 12 out of 28 students (42.86%) were categorized as active in the learning process. After the implementation of the SAVI model in the first cycle, student engagement increased to 67.86%, and in the second cycle, it further improved to 85.71%. The level of student engagement, which was initially dominated by the "fairly active" category, shifted to "active" and "very active" after the SAVI model was consistently applied and adjusted to students’ learning styles. These results demonstrate that the application of the SAVI model can effectively enhance students’ learning activity, as reflected in their increased participation in discussions, confidence in expressing opinions, and involvement in various learning activities. Therefore, the SAVI learning model is effective in creating an enjoyable, interactive, and participatory learning environment.Top of FormBottom of Form ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya partisipasi aktif siswa dalam proses pembelajaran.  Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Setiap siklus terdiri dari empat tahapan: perencanaan, pelaksanaan, observasi, dan refleksi. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi, sedangkan data dianalisis secara kuantitatif dan kualitatif. Penelitian ini bertujuan untuk meningkatkan keaktifan belajar siswa melalui penerapan model pembelajaran Somantis Auditori Visual Intelektual (SAVI) pada mata pelajaran Pendidikan Pancasila kelas V SDN Ciparay. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam keaktifan belajar siswa. Pada kondisi pra siklus, hanya 12 dari 28 siswa (42,86%) yang tergolong aktif dalam proses pembelajaran. Setelah penerapan model SAVI pada siklus I, terjadi peningkatan keaktifan siswa menjadi 67,86%. Kemudian, pada siklus II, keaktifan siswa meningkat lagi hingga mencapai 85,71%. Kategori keaktifan siswa yang semula didominasi oleh kategori “cukup aktif” meningkat menjadi “aktif” dan “sangat aktif” setelah model SAVI diterapkan secara konsisten dan disesuaikan dengan kebutuhan gaya belajar siswa. Hasil penelitian menunjukan bahwa penerapan model SAVI mampu meningkatkan keaktifan belajar siswa, yang ditunjukan melalui peningkatan partisipasi siswa dalam diskusi, keberanian mengemukakan pendapat, serta keterlibatan dalam berbagai aktivitas pembelajaran. Dengan demikian, model pembelajaran SAVI efektif digunakan untuk menciptakan pembelajaran yang menyenangkan, iteraktif, dan partisipasif.